Using Top-Down And Bottom-Up Strategy To Facilitate Students’ Listening Skill At The Eleventh Graders Of MA Mazro’illah Lubuklinggau - Intan Mawaddha; Dewi Syafitri; Hamdan Hamdan (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2024)
This research aims to prove whether top-down and bottom-up strategies can facilitate students' listening skills at level eleven of MA Mazro'illah Lubuklinggau. This research used pre-experimental methods. The population of this research was class XI MIPA students with a sample of 18 students. The sample used in this research was purpose sampling. In this study, researcher used written tests which were given twice, namely pre-test and post-test. In this study, researcher analyzed data using individual scores, normality tests and paired t-tests. The results of this study were that there were 4 students who passed and 14 students who failed the pre-test, while in the post-test the number of students who passed increased, namely 16 students and 2 students who failed the post-test. The students' average score on the pre-test was 48.05 and the average score on the post-test was 84.86. The results of the paired t-test is 8.53 and ttable is 1.740 it means that Ho is rejected and Ha is accepted. In conclusion it is significantly effective to use Top-down and Bottom-up strategy to facilitate students’ listening skill at the eleventh graders of MA Mazro’illah Lubuklinggau.